2014
DOI: 10.1158/1078-0432.ccr-14-0445
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biomarkers of Residual Disease after Surgical Debulking of High-Grade Serous Ovarian Cancer

Abstract: Purpose Residual disease (RD) following primary cytoreduction is associated with adverse overall survival in patients with epithelial ovarian cancer. Accurate identification of patients at high risk of RD has been elusive, lacking external validity and prompting many to undergo unnecessary surgical exploration. Our goal was to identify and validate molecular markers associated with high rates of residual disease. Methods We interrogated two publicly available datasets from chemonaïve primary high-grade serou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 27 publications
8
80
1
1
Order By: Relevance
“…6), in which these four genes were found to directly/indirectly interact with 15 TSGs and 25 oncogenes that all play important roles in the regulation of drug resistance in ovarian cancer (27,28). Consistent with our conclusions, the previous studies indicated that ADH1B and ABCA8 may be associated with drug resistance in ovarian cancer (45,46). ADH1B encodes a critical enzyme in alcohol metabolism, and may cause variations in the amount of production and/or oxidation of acetaldehyde between individuals (47).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…6), in which these four genes were found to directly/indirectly interact with 15 TSGs and 25 oncogenes that all play important roles in the regulation of drug resistance in ovarian cancer (27,28). Consistent with our conclusions, the previous studies indicated that ADH1B and ABCA8 may be associated with drug resistance in ovarian cancer (45,46). ADH1B encodes a critical enzyme in alcohol metabolism, and may cause variations in the amount of production and/or oxidation of acetaldehyde between individuals (47).…”
Section: Discussionsupporting
confidence: 89%
“…For example, ADH1B polymorphisms are associated with risk of head and neck (48), esophageal (49) and gastric cancer (50). In ovarian cancer, high ADH1B expression is associated with significantly higher risk of residual disease in high-grade serous ovarian cancer, and patients with high tumoral levels may be candidates for neoadjuvant chemotherapy (45). In addition, ADH1B is one gene in a group that encodes xenobiotic-metabolizing enzymes in pulmonary parenchyma and bronchial mucosa tissues from patients with non-small cell lung cancer (51).…”
Section: Discussionmentioning
confidence: 99%
“…There is a promising role for the development of novel molecular markers. For example, high levels of FABP4, a fatty acid binding protein, have been associated with residual disease after primary tumor debulking, and have also been noted to be upregulated in omental metastases [17,37]. Comparison of the performance among each newly-described tool is warranted and should identify the most accurate model estimating cytoreduction; addition of molecular markers may further refine these tools.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors felt that the addition of molecular markers or more advanced imaging studies could further increase accuracy and appropriate triage of patients to aggressive cytoreductive surgery [16]. A recent paper outlines the potential use for tumoral FABP4 as a molecular marker predictive of residual disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Development of genomic-based data to individualize therapy e PDS versus NACT [70] e is currently an area of active research and is likely to be a possibility in the near future.…”
Section: Resultsmentioning
confidence: 99%